Open Innovation for sustainable development goals: Learning from GoTo Group - Luthfiana Basyirah; Amilis Kina; Athi’ Hidayati (Faculty of Economics and Business, University of Muhammadiyah Malang, 2022)
This research aims to describe and provide experiences related to developing open innovation in digital business models to support sustainable development goals (SDGs). The research method is a literature study with a content analysis approach. First, we conducted a literature search on Google scholar and analyzed it using a descriptive-analytical method: data reduction, data presentation, and concluding. Furthermore, the conclusions from the literature review are used for assessing the GoTo Group business model. Our study finds that the GoTo Group implementation framework for sustainable development goals exists in three pillars - GoGreener, GoForward, and go together.